2010
DOI: 10.2310/jim.0b013e3181fa02f7
|View full text |Cite
|
Sign up to set email alerts
|

Airway Platelet Activation is Associated with Airway Eosinophilic Inflammation in Asthma

Abstract: Background-Allergic asthma is characterized by airway inflammation associated with recruitment and activation of eosinophils. In mice, allergen exposure induces platelet migration to the airways that is necessary for eosinophil recruitment and activation. We therefore hypothesized that in the airways of human subjects with asthma, (1) platelet activation would be positively associated with eosinophil activation and (2) platelet and eosinophil activation would both be associated with clinical asthma characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
0
26
0
2
Order By: Relevance
“…For every log 10 unit increase in CypA there was a 2.973 unit decrease in log 10 FEV 1 change with bronchodilator (−2.973 [−4.887, −1.059]; adjusted P =0.003), indicating a worse response to the bronchodilator drug. Based on recently published observations that platelet activation correlates with airway eosinophilia in asthma (25), we also examined whether levels of CypA or CypB might be associated with platelet activation in asthmatic airways. Both Cyps were associated with levels of P-selectin, which is a measurement of platelet activation (CypA: 0.418 [0.153, 0.683], adjusted P =0.002; CypB: 0.842 [0.018, 1.665]; adjusted P =0.045).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For every log 10 unit increase in CypA there was a 2.973 unit decrease in log 10 FEV 1 change with bronchodilator (−2.973 [−4.887, −1.059]; adjusted P =0.003), indicating a worse response to the bronchodilator drug. Based on recently published observations that platelet activation correlates with airway eosinophilia in asthma (25), we also examined whether levels of CypA or CypB might be associated with platelet activation in asthmatic airways. Both Cyps were associated with levels of P-selectin, which is a measurement of platelet activation (CypA: 0.418 [0.153, 0.683], adjusted P =0.002; CypB: 0.842 [0.018, 1.665]; adjusted P =0.045).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated not only that CypA can be released from activated platelets (46), but also that CypB increases platelet adhesion to collagen (47). Further, platelet activation has also been shown to be important for leukocyte activation and recruitment into tissues (25, 48). Thus, Cyps have the potential to be involved in many aspects of asthma pathology, from leukocyte activation and recruitment, to airway remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we demonstrated that TSLP could be induced to express in vascular endothelial and smooth muscle cells by angiotensin II and oxidized-low-density lipoprotein [26] and over-expressed in human atherosclerotic artery specimens [27], which indicated that TSLP/TSLPR might play roles in atherosclerosis. Therefore, TSLP is not only associated with inflammatory and allergy diseases but also plays important roles in atherosclerosis, which has been linked to platelet activation and the probability of thrombosis [28,29,30,31]. …”
Section: Introductionmentioning
confidence: 99%
“…20 Identifying the role of platelets in the development of allergic asthma will not only benefit our understanding of the molecular and cellular mechanisms of allergic asthma but may also provide potential targets for therapy of this disease. Although previous studies showed evidence of platelet activation, [21][22][23] as well as of the involvement of CD154 24 in asthma, the exact role of platelet activation and the underlying mechanisms in the progression of allergic asthma remain elusive.…”
Section: Introductionmentioning
confidence: 99%